Is your company ready for cloud? : choosing the best cloud adoption strategy for your business - Isom, Pamela (IBM Press, 2012)
"This book successfully addresses the approach for adopting cloud into organizations (small and large), realizing that every application may not be a fit for a cloud environment. The writer does an excellent job of integrating cloud into the approach for an enterprise architecture and drilling down into how to evaluate cloud in its variety of implementation techniques, along with the benefits and drawbacks of each."--Sue Miller-Sylvia, IBM Fellow and Vice President, Application Innovation Services, IBM Global Business Services Make the Right Cloud Adoption and Deployment Decisions for Your Business This is the first complete guide to cloud decision making for senior executives in both technology and non-technology roles. IBM® Global Business Services® Executive Architect Pamela K. Isom and IBM Fellow Kerrie Holley present practical business cases, vignettes, and techniques to help you understand when cloud investments make sense and when they don't. You'll find decision models that are anchored with practical experiences and lessons to guide your decision making, best practices for leveraging investments you've already made, and expert assistance with every aspect of the cloud transition. Drawing on their extensive experience working with enterprise clients, Isom and Holley show how to integrate both business and technical considerations, set the right priorities, and successfully manage everything from security and performance to governance. Whatever your company's size, industry, or challenges, this book will help you drive maximum business value from the cloud--on your terms and on your timeline. Coverage includes Assessing the business value of a cloud adoption strategy based on 10 specific expectations Gaining more value by incorporating cloud into enterprise architecture Implementing cloud when you don't already have an enterprise architecture Fully understanding the financial implications of cloud-based strategies and technologies Incorporating cloud in environments that have already adopted Service Oriented Architecture (SOA) Selecting components of your cloud portfolio, including elements of larger outsourced or managed solutions Governing cloud as part of your overall organizational landscape Systematically recognizing and mitigating cloud adoption risks, including security, cost, and performance Planning the transition: retiring legacy applications, transforming business processes, and selecting partners Anticipating and guidi ...